2015
DOI: 10.4103/2249-4863.161342
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of uncomplicated symptomatic urinary tract infections: Resistance patterns and misuse of antibiotics

Abstract: Introduction:Uncomplicated but symptomatic urinary tract infections (UTIs) are a common problem seen in practice. The study was undertaken to assess the most common pathogens responsible for uncomplicated symptomatic UTIs and the antimicrobial resistance pattern in a hospital in Bangalore. The study also explores the issue of antibiotic usage for these patients.Materials and Methods:The study was conducted in the Medicine department of a tertiary hospital in Bangalore. In all, 196 patients presented with sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
28
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 15 publications
11
28
3
1
Order By: Relevance
“…In a study conducted in India, it was observed that frequency rate for E.coli was 69.8% followed by Klebsiella to be 7.9%, 4.8% for Staphylococcus, 4.8% for Pseudomonas, 4.8% for Enterococcus and 1.6% for MRSA. (12) These results were comparable to our observations…”
Section: Discussionsupporting
confidence: 93%
“…In a study conducted in India, it was observed that frequency rate for E.coli was 69.8% followed by Klebsiella to be 7.9%, 4.8% for Staphylococcus, 4.8% for Pseudomonas, 4.8% for Enterococcus and 1.6% for MRSA. (12) These results were comparable to our observations…”
Section: Discussionsupporting
confidence: 93%
“…[26] The problems further worsen due to wrong management of the infection and/or over treatment. [13] Another revealing study showed 96% (4% gram positives) of total isolated microbes from UTI cases to be gram negative bacteria, among which E.coli was most prevalent. Upon antibiotic sensitivity testing of the isolates by disc-diffusion method with thirteen mechanistically different antibiotics, the gram negatives showed more resistance towards these antibiotics as compared to gram positive bacteria.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…[12] Another study done in medicine department at a tertiary hospital in Bangalore reported that gram negative bacteria constitute the largest group causing UTI (prevalence = 84.1%) with E.coli being the commonest (70%) uro-pathogen. [13] Problems associated with available treatment regime for E.coli infection: Apart from maintenance of adequate rehydration as primary treatment regime in case of E.coli diarrhea, a number of other treatment options are available for diverse range of pathogenic E.coli like antibiotic administration in case of extra-intestinal infections. [14] β-lactam antibiotics have been successfully used in such cases [15,16] [17] Emperical therapy failures are also common due to emergence of extended spectrum β-lactamases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary tract infections are the most common diseases encountered in the practice of medicine today [2], major cause of patient death and health care expenditure for all age groups, and it is estimated to account for more than seven million clinic visits and more than one million hospital admissions per year. The total cost of urinary tract infections to the United States health care system in 2000 was approximately 3.5 billion dollars.…”
Section: Introductionmentioning
confidence: 99%